(374) Principles of Unit Record Systems: Detail General Teaching Outline. مبادئ أنظمة تسجيل الوحدات: مخطط تدريس عام مفصل. - Selim, Salah. (The Institute Of National Planning., 2018)
this course is intended as an introduction to unit card record machine operation. and fundamental wiring concepts. no topic will be covered in depth.